Artificial Intelligence Based Drug Discovery Techniques for COVID-19 Detection - Arora, Kawal; Bist, Ankur Singh (Pandawan, 2020)
Recent advancements in the area of drug discovery using artificial intelligence made it possible to speed up the hunt for new pharmaceuticals. Drugs like arbidol, atazanavir, remdesivir & favipiravir are under testing phase to cure COVID-19. In this paper, we present systematic study of AI based drug discovery techniques suitable for COVID-19 detection.